A Mushroom Extract Piwep from Phellinus igniarius Ameliorates Experimental Autoimmune Encephalomyelitis by Inhibiting Immune Cell Infiltration in the Spinal Cord. (27th January 2014) - Li, Lan; Wu, Guang; Choi, Bo Young; Jang, Bong Geom; Kim, Jin Hee; Sung, Gi Ho; Cho, Jae Youl; Suh, Sang Won; Park, Hyoung Jin
Abstract : The present study aimed to evaluate the therapeutic potential of a mushroom extract from Phellinus igniarius in an animal model of multiple sclerosis. The medicinal mushroom, Phellinus igniarius, contains biologically active compounds that modulate the human immune system. Experimental autoimmune encephalomyelitis (EAE) was induced by immunization with myelin oligodendrocyte glycoprotein (MOG 35–55) in C57BL/6 female mice. A water-ethanol extract of Phellinus igniarius (Piwep) was delivered intraperitoneally every other day for the entire experimental course. Three weeks after the initial immunization, demyelination and immune cell infiltration in the spinal cord were examined. Piwep injection profoundly decreased the daily incidence rate and clinical score of EAE. The Piwep-mediated inhibition of the clinical course of EAE was accompanied by suppression of demyelination and infiltration of encephalitogenic immune cells including CD4+ T cells, CD8+ T cells, macrophages, and B cells in the spinal cord. Piwep reduced expression of vascular cell adhesion molecule-1 (VCAM-1) in the spinal cord and integrin-α 4 in the lymph node of EAE mice. Piwep also inhibited proliferation of lymphocytes and secretion of interferon-γ in the lymph node of EAE mice. The results suggest that a mushroom extract, Piwep, may have a high therapeutic potential for ameliorating multiple sclerosis progression.